2007
DOI: 10.1007/s11239-006-0002-8
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation treatment for the reduction of stroke in atrial fibrillation: a cohort study to examine the gap between guidelines and routine medical practice

Abstract: This study presents 'real-life' data in treating patients with AF in Germany and identifies the potential to advance the quality of care with respect to anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 35 publications
4
27
1
4
Order By: Relevance
“…Only 3 articles reported on cohorts including subjects receiving different VKAs (including warfarin), 14 -16 and the VKA used was not reported in 1 article. 17 Thirty-two articles used a target range of 2.0 to 3.0, and 6 articles 18 -23 reported slight variations on this range (ie, 2.0 to 3.5).…”
Section: Resultsmentioning
confidence: 99%
“…Only 3 articles reported on cohorts including subjects receiving different VKAs (including warfarin), 14 -16 and the VKA used was not reported in 1 article. 17 Thirty-two articles used a target range of 2.0 to 3.0, and 6 articles 18 -23 reported slight variations on this range (ie, 2.0 to 3.5).…”
Section: Resultsmentioning
confidence: 99%
“…This overall standard of INR control seems better than in usual clinical practice, which often reports lower TTR. [18][19][20][21] However, in sites and countries with a more optimal anticoagulation service, even better results can be achieved. 22 The median TTR in ARISTOTLE was similar to that observed in several previous open-label warfarin controlled trials 10,11,23 and higher than that observed in a previous double-blind trial.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies did not reflect routine care (7,8), failed to include elderly AF patients (9) or were limited by low numbers of AF cases (9,10). Moreover, the proportion of AF patients receiving antithrombotic drugs was possibly overestimated, since field studies based on voluntary participation of the treating physicians may have overrepresented those who already provide adequate antithrombotic treatment to their AF patients (7,8,10,11).…”
Section: Introductionmentioning
confidence: 99%